Normalized Multipotential Redox Coding of DNA Bases for Determination of Total Nucleotide Composition - Kodr, David; Ortiz, Mayreli; Sýkorová, Veronika; Yenice, Cansu Pinar; Lesnikowski, Zbigniew J; O'Sullivan, Ciara K; Hocek, Michal (Analytical chemistry, 2023)
The previously reported approach of orthogonal multipotential redox coding of all four DNA bases allowed only analysis of the relative nucleotide composition of short DNA stretches. Here, we present two methods for normalization of the electrochemical readout to facilitate the determination of the total nucleotide composition. The first method is based on the presence or absence of an internal standard of 7-deaza-2'-deoxyguanosine in a DNA primer. The exact composition of the DNA was elucidated upon two parallel analyses and the subtraction of the electrochemical signal intensities. The second approach took advantage of a 5'-viologen modified primer, with this fifth orthogonal redox label acting as a reference for signal normalization, thus allowing accurate electrochemical sequence analysis in a single read. Both approaches were tested using various sequences, and the voltammetric signals obtained were normalized using either the internal standard or the reference label and demonstrated to be in perfect agreement with the actual nucleotide composition, highlighting the potential for targeted DNA sequence analysis.
Keywords: DNA; Nucleotides; nukleotidy; Oxidation-Reduction; oxidace-redukce; DNA primery; DNA Primers